Giant Nonlinear Hall Effect Induced Ultrahigh Rectification in a Weyl Semiconductor - Hao Liu; Ting Yong Lim; Shijia Tian; Jinfeng Zhai; Du Xiang; Tao Liu; Tay‐Rong Chang; Pan He; Jian Shen (Advanced Electronic Materials)
Abstract Conventional diode‐based rectifiers suffer from limited applicability in low‐power electronics and high‐frequency wireless networks due to their inherent junction structures. Recent studies have demonstrated that the nonlinear Hall effect (NHE) in non‐centrosymmetric quantum materials can enable diode‐free rectification with advantages such as large active area, low power threshold, and high cutoff frequency. Here, a giant NHE is reported in a chiral semiconductor hosting Weyl nodes, achieving a voltage responsivity of up to 1.4×107 V W−1 at low temperature and 1.7×106 V W−1 at room temperature. This represents orders of magnitude improvement over existing NHE rectifiers and commercial Schottky diodes. This ultrahigh rectification is attributed to the significant contributions of Weyl nodes at the conduction band edge. Moreover, the device exhibits remarkable tunability through electrostatic gate voltages. The findings establish Weyl semiconductors as a promising platform for developing highly sensitive NHE rectifiers for low‐power and high‐frequency applications.